Molecular Docking and Thermodynamic Studies of the Interactions between Aspirinate Complexes of Transition metals and Cyclooxygenase-2 Enzyme: Quantum Chemical Calculations based on the ONIOM method - Maryam Mortazavi; Amirhossein Sakhteman; Anahita Hessami; Hossein Sadeghpour (Shiraz University of Medical Sciences, 2017)
In the present research, molecular docking and thermodynamic properties of the transition metal complexes of aspirin were calculated against Cyclooxygenase-2 (COX-2) enzyme.  Density functional theory with dispersion function (DFT-D) using LANL2DZ basis set calculation was carried out to study the structural and thermodynamic properties of the interaction between aspirinate complexes of transition metals and COX-2. The ONIOM2 (wB97X-D/LANL2DZ:UFF) method was applied to the interaction of transition metal complexes with COX-2 binding site. The Interaction enthalpies and the Gibbs free energies between aspirinate complexes of Cu(II), Zn(II), Fe(III), and In(III) as anti-inflammatory complexes and COX-2  enzyme in the gas phase were calculated. The structure as well as the thermodynamics of optimized metal complexes was debated from the biological point of view. In the gas phase, the interaction was relatively strong and transition metal complexes could be used as potential anti-inflammatory drugs.